Empirical Analysis on the Effect of Agricultural Insurance on Production——Based on panel data of 31 provinces and cities in China from 2008 to 2018 - Caifei Lv (E3S Web of Conferences, 2020)
This paper uses panel data of Insurance Statistics Yearbook and the National Bureau of Statistics of China in 31 provinces and cities from 2008 to 2018. The random effects model is used to study the direction and intensity of agricultural production impacts from agricultural insurance and its compensation. The collinearity robustness and endogeneity tests are carried out as the empirical results. It shows that agricultural insurance has a significant promotion effect on the agricultural output, and its influence will increase with the growth of risks. From the regional sub-sample regression results, agricultural insurance in the central and eastern of China is more significant than the western. Therefore, China should continue to vigorously promote the reform and innovation of agricultural insurance and its system, expand the coverage of agricultural insurance, and accelerate its high-quality.